The evolutionary significance of certain amino acid substitutions and their consequences for HIV-1 immunogenicity toward HLA's A*0201 and B*27 - Hecht, Luke (Biomedical Informatics, 2013)
In silico tools are employed to examine the evolutionary relationship to possible vaccine peptide candidates' development. This perspective sheds light on the proteomic changes affecting the creation of HLA specific T-cell stimulating peptide vaccines for HIV. Full-length sequences of the envelope protein of the HIV subtypes A, B, C and D were obtained through the NCBI Protein database were aligned using CLUSTALW. They were then analyzed using RANKPEP specific to Human Leukocyte Antigen A*02 and B*27. Geneious was used to catalogue the collected gp160 sequences and to construct a phylogenic tree. Mesquite was employed for ancestral state reconstruction to infer the order of amino acid substitutions in the epitopes examined. The results showed that consensus peptide identified SLAEKNITI had changes that indicated predicted escape mutation in strains of HIV responding to pressure exerted by CD8+ cells expressing HLA A*02. The predominating 9-mers IRIGPGQAF of gp120 are significantly less immunogenic toward HLA B*27 than to HLA A*02. The data confirms previous findings on the importance for efficacious binding, of an arginine residue at the 2(nd) position of the gag SL9 epitope, and extends this principle to other epitopes which interacts with HLA B*27. This study shows that the understanding of viral evolution relating T-cell peptide vaccine design is a development that has much relevance for the creation of personalized therapeutics for HIV treatment.